(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this article, the effects of different concentrations of heavy metals Cu (II), Co(II) and Cd(II) cations and NaCl salt stress on the morphological characteristics, biomass, chlorophyll a, exopolysaccharides and phytohormones production capacity of native salt-tolerant nitrogen-fixing cyanobacteria Nostoc calcicola 25 and Anabaena variabilis 21 strains observed. It was found that the strains were resistant to NaCl concentration from 100 to 800 mmol/L and maintained a sufficient amount of biomass at NaCl concentration from 100 to 500 mmol/L. Nostoc calcicola 25 and Anabaena variabilis 21 strains can synthesize exopolysaccharide, gibberellin and IAA under the influence of salinity with NaCl and heavy metals. Specifically, Nostoc calcicola 25 strain indole-3-acetic acid production was 117 mg/l at Cu (II) 20 mmol/L and tryptophan 2.5 mg/ml concentration, 98 mg/l Cu (II) at 20 mmol/L and 0.5 mg/ml tryptophan concentration, gibberellin content at Cu (II) 20 mmol/L was 39 mg/L. Anabaena variabilis 21 produced exopolysaccharides 5 times higher than the control on the 5th day of cultivation at 200 mmol/L salinity and 50 mmol/L Cd (II). The obtained results make it possible to create biological fertilizers for remediation of saline soils contaminated with heavy metals based on local strains of cyanobacteria and to recommend them for practice.